Implementasi Metode Talqiyan Fikriyan pada Pembelajaran Tsaqofah Islam - Fikri Aziz; Ferli Septi Irwansyah (Jurnal Perspektif, 2019)
Home Schooling Group Generasi Pemimpin Cemerlang Bandung is a school that gave rise to a new learning method, the talqiyan fikriyan method. This study aims to determine the talqiyan fikriyan method in Islamic thaqofah subjects; implementation of talqiyan fikriyan method in Islamic thaqofah subjects. The research method used is qualitative research with the type of field research. In collecting the data using participant observation techniques, in-depth interviews (principals and Islamic thaqofah subject teachers) coupled with the practice of Islamic thaqofah lessons from students at school. From the research results obtained, it was concluded that the talqiyan fikriyan method is a learning method that seeks to build students' thinking abilities in sensing what the teacher teaches directly towards the creed and practice; in the learning evaluation process, the teacher measures the level of student success in understanding the material, namely the oral test and the performance test).